Ultrasonic Assisted Synthesis, Biological Evaluation, and Molecular Docking of Chalcone-based 1,5-benzodiazepine as Potential Anticonvulsant Agents - Rajkumar, Thangavelu; Kumar, Solleti V. Suresh; Srinivasan, Nagarajan (Current Enzyme Inhibition, 2022)
Background: Epilepsy is a constant neurological disorder influencing around 50 million individuals globally. However, most epileptic patients do not react to accessible medications and clinical treatments. This research work has been planned to produce novel 1,5-benzodiazepines from chalcone intermediates by ultrasonic irradiation method and perform the anticonvulsant activity by pentylenetetrazole incited seizures tests. Methods: Chalcones are used as precursors for synthesizing 1, 5-benzodiazepines by a reaction with ophenylenediamine in absolute ethanol in the presence of glacial acetic acid as a catalyst. The proposed synthesized structures were characterized by melting point, TLC, FTIR, 1H & 13CNMR, and mass spectroscopy. All the molecules were assessed for anticonvulsant activity. Results: Anticonvulsant activity uncovered the fact that the mixes derived from dimethylamino, dimethoxy, hydroxy-substituted chalcones in the 1, 5-benzodiazepines can be used for seizures in mice. These pharmacological examinations have shown that these new subsidiaries can repress seizures incited by pentylenetetrazole in mice proficiently. Our molecular docking studies also supported probable effects. Conclusion: The results are promising, which on further assessments may provoke medicine particles against seizures in mice.
Keywords: Anticonvulsant